Fachsprache Französisch – facettenreich, faszinierend, funktional - Gerzymisch, Heidrun; Nord, Christiane; Blumenthal, Peter; Lüger, Heinz-Helmut; Polzin-Haumann, Claudia; Adamzik, Kirsten; Eggensperger, Karl-Heinz; Neumann, Sybille; Eckkrammer, Eva Martha; Dethloff, Uwe; Schmale, Günter; Rentel, Nadine (htw saar (Prof Thomas Tinnefeld), 2025)
This volume offers a scholarly investigation of French for Specific Purposes (FSP), addressing the phenomenon in its linguistic diversity, discursive functionality, and disciplinary relevance. The contributions examine the specialised use of French from both theoretical and applied perspectives, engaging with key domains such as terminology, stylistics, professional communication, corpus analysis, didactics, and translation studies.